Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T22:49:17+01:00
A)
-(x+1)-2(y+1)=-5
3x+5y=7

-x-1-2y-2=-5
3x+5y=7

-x-3-2y=-5
3x+5y=7

-x-2y=-2/*3
3x+5y=7

-3x-6y=-6
3x+5y=7

-3x-6y+3x+5y=-6+7
-y=1/*(-1)
y=-1
3x+5*(-1)=7
3x-5=7
3x=12/:3
x=4
x=4
y=-1

b)
2(x-3)+(y-5)=-4
x+2y=14

2x-6+y-5=-4
x+2y=14

2x-11+y=-4
x+2y=14

2x+y=7/*(-2)
x+2y=14

-4x-2y=-14
x+2y=14

-4x-2y+x+2y=-14+14
-3x=0/:(-3)
x=0

0+2y=14
2y=14/:2
y=7
x=0
y=7
2010-01-19T22:52:22+01:00
1) -(x+1)-2(y+1)=-5
3x+5y=7

-x-1-2y-2=-5
3x+5y=7

-x-2y=-2 /x3
3x+5y=7

-3x-6y=-6
3x+5y=7
___________
+
= -y= 1
y= -1

3x+5y=7
3x=7 - (5x-1)
3x = 7 + 5
3x = 12
x = 4

x = 4
y= -1




2) 2(x-3)+(y-5)=-4
x+2y=14

2x-6+y-5=-4
x+2y=14

2x-11+y=-4
x+2y=14

2x+y = 7
x+2y=14 /x(-2)

2x+y=7
-2x-4y=-28
+__________
= -3y = -21
y = 7


2x + 7 = 7
2x = 0
x = 0


x = 0
y = 7


2010-01-19T22:59:28+01:00
A)
-(x+1)-2(y+1) =-5
3x+5y=7

-x -1 - 2y - 2 = -5
3x + 5y = 7

- x -2y = -2 /*5
3x + 5y = 7 /*2

-5x - 10y = -10
6x + 10y = 14
..................
x = 4

3x + 5y = 7
3 *4 + 5y = 7
5y = 7 - 12
y = -1

b)
2(x-3)+(y-5)=-4
x+2y=14

2x - 6 + y - 5 = -4
x + 2y = 14

2x + y = 7
x + 2y = 14 /* (-2)

2x + y = 7
-2x -4y = -28
...................
-3y = -21 /:(-3)
y = 7

2x + y = 7
2x + 7= 7
2x = 0
x = 0